2018
DOI: 10.1007/s40266-018-0555-1
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of ABCB1 and CYP2C19 Genetic Variants Predicts Risk of Major Bleeding and Thrombotic Events in Elderly Patients with Acute Coronary Syndrome Receiving Dual Antiplatelet Therapy with Aspirin and Clopidogrel

Abstract: ObjectiveThe clinical efficacy of clopidogrel in secondary prevention of vascular events is hampered by marked inter-patient variability in drug response, which partially depends on genetic make-up. The aim of this pilot prospective study was to evaluate 12-month cardiovascular outcomes in elderly patients with acute coronary syndrome (ACS) receiving dual antiplatelet therapy (aspirin and clopidogrel) according to the clustering of CYP2C19 and ABCB1 genetic variants.MethodsParticipants were 100 consecutive ACS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
4
1
1
Order By: Relevance
“…In contrast, CYP2C19 *17, known as a functional acquired gene mutation, is associated with an increased risk of bleeding. 29 Our study did not observe that the CYP2C19 2 *3 * and 17 * alleles were associated with gastric mucosal erosion but found that ABCB1 3435T allele carriers had a higher incidence of gastric mucosal erosion after long-term clopidogrel use. ABCB1 is also known as the multidrug resistance gene MDR1, and its encoded P-glycoprotein can pump harmful substances or substrates, such as drugs, out of the cell.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In contrast, CYP2C19 *17, known as a functional acquired gene mutation, is associated with an increased risk of bleeding. 29 Our study did not observe that the CYP2C19 2 *3 * and 17 * alleles were associated with gastric mucosal erosion but found that ABCB1 3435T allele carriers had a higher incidence of gastric mucosal erosion after long-term clopidogrel use. ABCB1 is also known as the multidrug resistance gene MDR1, and its encoded P-glycoprotein can pump harmful substances or substrates, such as drugs, out of the cell.…”
Section: Discussioncontrasting
confidence: 87%
“…In contrast, CYP2C19 *17 , known as a functional acquired gene mutation, is associated with an increased risk of bleeding. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that evaluated the association between genetic variations and clinical outcomes have mainly focused on ischemic outcomes such as cardiac death, myocardial infarction, stent thrombosis, and target lesion revascularization 12 . CYP2C19 is the most commonly studied gene, and several studies on this gene have shown that the gain-of-function group had a higher occurrence of bleeding events than the loss-of-function group 7 , 13 . However, the prevalence of gain-of-function in Asians with the CYP2C19 variant is very low compared to that in Caucasians with the CYP2C19 variant 8 , 14 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Помимо аллельных вариантов, ответственных за ослабление эффекта клопидогрела, был выявлен полиморфизм CYP2C19*17, гомозиготный вариант которого ассоциировался с повышением риска кровотечений [39][40][41][42]. Возможно, однако, что для данного аллельного варианта имеет значение этническая принадлежность.…”
Section: клопидогрелunclassified